A comparative assessment of the awareness of danger signs and practice of birth preparedness and complication readiness among pregnant women attending rural and urban general hospitals in Lagos State - Babatope Oni; Oluwakemi Ololade Odukoya; Adeyemi Adebola Okunowo; Omobola Y Ojo; Yetunde O Abatan (Sahel Medical Journal, 2016)
Background: Nigeria still experiences a high burden of unsafe motherhood. The knowledge of obstetric danger signs and the effective application of the principles of birth preparedness and complication readiness (BPACR) have the potential to significantly reduce the high maternal and perinatal morbidity and mortality rates. However, rural-urban differences may exist in the knowledge and practice of  BPACR among women, and these may limit its potential benefit. We set out to assess and compare the knowledge of obstetric danger signs and practice of BPACR among pregnant women attending Rural (Agbowa) and Urban (Gbagada) Hospitals in Lagos State. Materials and Methods: In this cross-sectional comparative study, pregnant women attending antenatal clinics in each health facility were recruited into the study using a systematic sampling method. A structured interviewer administered questionnaire adapted from the safe motherhood John Hopkins Program for International Education in Gynecology and Obstetrics prototype questionnaire was used for data collection. Data were analyzed using SPSS version 17.0. Results: Awareness of obstetric danger signs during pregnancy was good among rural and urban study participants accounting for 62.4% and 68.4%, respectively. The most commonly identified danger sign in pregnancy, labor, and after delivery was bleeding from the genital tract. The awareness of danger signs during labor and after delivery identified by the women was low in both settings, though relatively higher in the urban area. The level of BPACR was low in both groups of women but was higher among women attending the urban center (31.6%) compared with the rural center (13.2%) P-value < 0.001. Conclusion and Recommendations: Activities aimed at improving birth preparedness practices particularly among rural women should be considered.